Integrated supply of stemwood and residual biomass to forest-based biorefineries. Issue 2 (3rd May 2016) - Joelsson, Jonas; Di Fulvio, Fulvio; De La Fuente, Teresa; Bergström, Dan; Athanassiadis, Dimitris
ABSTRACT: The demand for forest biomass as raw material for a wide range of products in the developing bioeconomy is expected to increase. Along with a constant pressure on forestry to increase its productivity, this development has led to the search for new procurement methods and new assortments. The present study assessed innovative supply chain practices, with a particular focus on the integrated supply of stemwood and residual tree parts. The assortments considered included tree sections, long tops, saw logs with stump cores and small whole trees from thinnings. The assessment included geographically explicit modelling of the supply chain operations and estimation of supply cost and energy use for three industrial locations in Northern Sweden. The innovative supply chains were compared to conventional, separate, harvest of stemwood and logging residues. We conclude that integrated harvest of tops and branches with stemwood assortments, as well as whole-tree harvest in early thinnings, has a significant potential to reduce the supply cost for the non-stemwood assortments. Stump wood generally remains the most expensive assortment. The energy use analysis confirms earlier research showing that the energy input is relatively small compared to the energy content of the harvested feedstock. ABBREVIATIONS BWT, bundled whole trees; CTL, cut-to-length; ET, energy thinning; FF, final felling; FT, first thinning; LR, logging residues; LT long tops; ORN, Örnsköldsvik; PCT, pre-commercial thinning; PL, pulpwood; RS, roughly delimbed tree sections; SEK, Swedish currency; SFA, Swedish Forest Agency; SL, sawlogs; SNFI, Swedish National Forest Inventory; SP, stumps; SPC stump core; ST, second thinning; STO, Storuman; UME Umeå; WT, whole small trees;